2023
DOI: 10.1093/rheumatology/kead118
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset gout and rare deficient variants of the lactate dehydrogenase D gene

Abstract: Objectives To investigate whether lactate dehydrogenase D (LDHD) gene deficiency causes juvenile-onset gout. Methods We used whole exome sequencing (WES) for two families and a targeted gene-sequencing panel for an isolated patient. D-lactate dosages were analyzed by using ELISA. Results We demonstrated linkage of juvenile-onset gout to homozygous carriage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…• The prevalence of gout and its incidence is steadily increasing all around the world with an important rise on annual incidence rates in the Middle East and North Africa region (6). High D-lactate levels in the blood and/ or urine due to these mutations may lead to gouty arthropathy (12). Another study has found associations between gene expression of inflammatory regulators including free fatty acid receptor 2 (FFAR2) and suppressor of cytokine signalling 3 (SOCS3), and gout flares, suggesting a role in the initiation and resolution of flare, respectively (13).…”
Section: Take-home Messagesmentioning
confidence: 99%
“…• The prevalence of gout and its incidence is steadily increasing all around the world with an important rise on annual incidence rates in the Middle East and North Africa region (6). High D-lactate levels in the blood and/ or urine due to these mutations may lead to gouty arthropathy (12). Another study has found associations between gene expression of inflammatory regulators including free fatty acid receptor 2 (FFAR2) and suppressor of cytokine signalling 3 (SOCS3), and gout flares, suggesting a role in the initiation and resolution of flare, respectively (13).…”
Section: Take-home Messagesmentioning
confidence: 99%